Synthetic cannabinoid availability on darknet drug markets—changes during 2016–2017. Issue 1 (1st January 2019) - Scourfield, Andrew; Flick, Catherine; Ross, Jack; Wood, David M.; Thurtle, Natalie; Stellmach, Darryl; Dargan, Paul I.
Abstract: Changes in legislation have affected supply routes of new psychoactive substances such as synthetic cannabinoids with evidence of supply over the darknet. We identified darknet drug markets using an index database and Tor Browser to access markets. We identified SC in product listings using a custom-programmed script. We collected data at bimonthly intervals (August 2016–April 2017). Eleven darknet markets listed SC for sale, the largest number from China, UK, US, Netherlands, and Germany. Formulations available were high purity powder/crystal, smoking preparations and vape preparations. The top five listed compounds from China across the time points were FUB-AMB, ABD-FUBINACA, 5F-NPB-22, MAB-CHMINACA, and NM-2201. 5F-CUMYL-4CN-PINACA was unavailable at early time points but emerged during the study. Cost of high purity formulations from China ranged from 1.3 to 3.1 Euro per gram for quantities ≥1000 g. Europe and North America accounted for 99% smoking preparations predominantly in small packages (<50 g). SC are widely available on the darknet with availability changing over time. High purity formulations are predominantly available from China in quantities up to kilograms with price per gram reducing with increased quantity. Small packages of ready-made smoking mixtures are available from Europe and North America.